Connexins and Pannexins: New Insights into Microglial Functions and Dysfunctions - Gajardo-Gómez, Rosario; Labra, Valeria C.; Orellana, Juan A. (Frontiers in Molecular Neuroscience, 2016)
In a physiological context, microglia adopt a resting phenotype that is associated with the production of anti-inflammatory and neurotrophic factors. In response to a wide variety of insults, they shift to the activated phenotype that is necessary for the proper restoration of brain homeostasis. When the intensity of the threat is relatively high, microglial activation can worsen the damage progression instead of providing protection, with potentially significant consequences for neuronal survival. Coordinated interactions among microglia and with other brain cells, including astrocytes and neurons, is critical for the development of timely and optimal inflammatory responses in the brain parenchyma. Tissue synchronization is in part mediated by connexins and pannexins, which are protein families that form different plasma membrane channels to communicate with neighboring cells. At one end, the gap junction channels (which are exclusively formed by connexins in vertebrates) connect the cytoplasm of contacting cells to coordinate electrical and metabolic coupling. At the other end, hemichannels and pannexons (which are formed by connexins and pannexins, respectively) communicate via intra- and extracellular compartments and serve as diffusion pathways for the exchange of ions and small molecules. In this review, we discuss the evidence available concerning the functional expression and regulation of connexin- and pannexin-based channels in microglia and their contribution to microglial function and dysfunction. We focus on the possible implications of these channels in microglia-to-microglia, microglia-to-astrocyte and neuron-to-microglia interactions in the inflamed brain.